1994
DOI: 10.1071/pp9940875
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Variation During Grain Filling and Changes in Wheat-Grain Quality

Abstract: There have been a few notable occasions when the Australian wheat segregation system (mainly based on specification of variety and protein content) has failed to produce grain which gives dough properties expected for the wheat grade. The reasons for this are likely to relate to growing and storage conditions; of these, variations in temperature during grain filling appear to be a major factor. Observations of crop statistics, field and glasshouse experiments indicate that as growth temperatures increase up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 9 publications
4
37
1
2
Order By: Relevance
“…During grain filling, the modifications in the grain protein content (Table 3), associated with high temperatures (> 30ºC), have been related to reductions in the sedimentation index SDS (Graybosh et al, 1995) and seemed to promote a decrease in gluten strength. Data obtained in several studies carried out in the field and confirmed under controlled environments (Blumenthal et al, 1993;Stone and Nicolas, 1994;Wrigley et al, 1994;Panozzo and Eagles, 2000), indicate that a few days of maximum daily temperatures surpassing 32ºC produce grains with weaker dough. This effect on the dough properties, involving modifications in the protein composition associated with high temperatures during grain growth has also been pointed out by several authors (Blumenthal et al, 1993;Wrigley et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During grain filling, the modifications in the grain protein content (Table 3), associated with high temperatures (> 30ºC), have been related to reductions in the sedimentation index SDS (Graybosh et al, 1995) and seemed to promote a decrease in gluten strength. Data obtained in several studies carried out in the field and confirmed under controlled environments (Blumenthal et al, 1993;Stone and Nicolas, 1994;Wrigley et al, 1994;Panozzo and Eagles, 2000), indicate that a few days of maximum daily temperatures surpassing 32ºC produce grains with weaker dough. This effect on the dough properties, involving modifications in the protein composition associated with high temperatures during grain growth has also been pointed out by several authors (Blumenthal et al, 1993;Wrigley et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Data obtained in several studies carried out in the field and confirmed under controlled environments (Blumenthal et al, 1993;Stone and Nicolas, 1994;Wrigley et al, 1994;Panozzo and Eagles, 2000), indicate that a few days of maximum daily temperatures surpassing 32ºC produce grains with weaker dough. This effect on the dough properties, involving modifications in the protein composition associated with high temperatures during grain growth has also been pointed out by several authors (Blumenthal et al, 1993;Wrigley et al, 1994). The lack of interaction genotype x treatment for protein content in the bread wheat, and also in SDS for the bread and durum wheat (Table 3), might indicate an absence of genetic variability in the response of these traits to high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the increase in temperature (2-4°C) had a larger effect than elevated CO 2 on grain quality (Tester et al 1995;Williams et al 1995). Moreover, the effects of elevated CO 2 on grain quality may be partially balanced because temperature increase can enhance grain protein content (Randall and Moss 1990;Wrigley et al 1994). …”
Section: Introductionmentioning
confidence: 95%
“…Heat shock takes different forms, which are characterized by timing (days after anthesis) and by duration, which may also gave rise to different effects on the durum wheat quality (Corbellini et al, 1997). A "strengthening" effect has been observed with chronic heat stress whereas heat shock may have a "weakening" effect, both in common and durum wheat (Borghi et al, 1995;Wardlaw and Wrigley, 1994;Wrigley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%